Thermal analysis and x-ray diffraction of rice husk ash blended cement under sodium sulfate with wetting and drying cycles - Putra Jaya, Ramadhansyah; M. R., Hainin; O., Rokiah; Ramli, Noram Irwan; W. I., Mohd Haziman; S. A., Mangi (Springer, 2021)
Sulfate attack is one of the most aggressive environmental deterioration affecting the durability of concrete structures. Thus, this study is to evaluate the effect of sodium sulfate (5% Na2SO4) solution on the performance of rice husk ash (RHA) blended cement under drying and wetting cycle, which is thought to simulate an aggressive environment in concrete. The RHA replacement level used was 10%. The performance of the specimen was evaluated by the differential thermal analysis (DTA), thermogravimetric analysis (TGA), and X-ray diffraction (XRD). The results showed that the replacement of ordinary Portland cement by 10% rice husk ash effectively improved the resistance of concrete due to sulfate attack. The result also indicate that the quantity of expansive gypsum formed by the reaction of calcium hydroxide will be less in RHA blended cement than in OPC specimen. In addition, RHA blended cement possibly reduced the potential of ettringite and gypsum formation due to the reduction in the quantity of calcium hydroxide, thus, improved the resistance of concrete to sulfate attack.